A Qualitative Study of the Argumentative Text in the Film Pengkhianatan G30S/PKI and Its Influence on the Understanding of National History - Nadra Amalia; Ajeng Novita Aprilia; Josepin Manalu; Syarifah Nurmasyittah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to describe the form of argumentative text in the film Pengkhianatan G30S/PKI, analyze its influence on the understanding of national history, and determine the audience's interpretation of the historical narrative presented in the film. The study uses a descriptive qualitative method with the object of research being the film Pengkhianatan G30S/PKI which is used as a stimulus media in building an understanding of national history. The study involved five informants who were asked to watch the film in its entirety and write an argumentative text in the form of cause and effect based on their understanding of the film's content. Data collection techniques were carried out through observation, interviews, documentation, and literature studies. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, as well as drawing conclusions and verification. The results of the study show that the film Pengkhianatan G30S/PKI contains various forms of argumentative text constructed through dialogue, narration, character depiction, and visual scenes that tend to use a cause and effect pattern. The film has an influence on the understanding of national history because it is able to shape the audience's perception and interpretation of historical events. In addition, films also have relevance to history education as a learning medium that can increase students' interest and understanding, although their use needs to be accompanied by a critical approach to avoid a one-sided understanding of history.